The role and place of the individual peasant farms in the economic sustenability of the rural population in Romania - Aurel Lup (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The paper is a analyse of the exploitation structures, the evolution of the land resource in the agriculture focussed on the part and place of the individual-peasant farms in agricultural economy of Romania. The farms were grouped by size and in each group is calculated the weight in agricultural aria, average size in hectares, number of the animals for the main species average per farm, density per 100 ha. Is compared economic performances of the individual peasant farms with those of the units with legal status, great sized. On the basis of the results obtained is evident the economic and social role of the individual peasant farms in sense off the durable rural development concept. Is proposed adjustment of much support for the purpose of increasing the performances of this category of farms inclusively by increasing their size.
Keywords: 330; individual; farm; rural population; rural development; performances; market economy.